Gendered Agency in Spice Trade Histories: Female Stewardship of Islamic Gastronomic Traditions in the Nusantara Archipelago - Wardah, Eva Syarifah; Fauziyah, Siti; Hujjah, Wasithotul; Akosmanoğlu, Tuğçe; Belgasem, Hanan Salem Masoud; Voeut, Nasri (JURNAL INDO-ISLAMIKA, 2025)
During the Sultanate era, Banten emerged as a global spice emporium, attracting international traders through its pepper-dominated 16th-century economy. Though its prominence in the spice trade has waned, historical traces persist through preserved heritage and enduring culinary traditions rooted in spice culture. This study employs qualitative methods and a cultural-historical approach within the Islam Nusantara framework to analyze women’s pivotal role in sustaining Banten’s spice-based culinary practices. As guardians of traditional recipes, healers, and perfumers, women preserve spiritual and health values tied to spices. Findings reveal their multifaceted contributions—from agricultural cultivation and post-harvest processing to local commerce—while embedding spices into religious rituals, spiritual healing, and cultural traditions. These activities enrich the symbolic significance of spices and reinforce community identity. Women’s strategic participation not only sustains the archipelago’s spice civilization but also bolsters the local economy, demonstrating how cultural stewardship aligns with Islamic principles of community welfare. This research underscores the intersection of gender, cultural preservation, and economic resilience in maintaining Indonesia’s spice heritage.